AN ANALYSIS OF FIQH SIYASAH ON ENVIRONMENTAL MANAGEMENT AND PROTECTION THROUGH THE IMPLEMENTATION OF REGIONAL REGULATION NO. 19 OF 2018 IN JENEPONTO REGENCY - Bashar, Nur Alif; A Rahman, Budiarti; Mustafa, Adriana (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2025)
The implementation of the Jeneponto Regency Regional Regulations is often hampered in its implementation. This study aims to determine how the implementation of Regional Regulation no. 19 of 2018 at the Jeneponto Regency Environmental Service and also to study fiqh siyasah analysis of environmental management and protection through the application of regional regulation no. 19 of 2018 in Jeneponto district. This type of research uses qualitative research with descriptive methods. There are two sources of data used, namely primary data sources and secondary data sources. From this study it was found that the implementation of the Jeneponto Regency regional regulation Number 19 of 2018 concerning environmental management and protection was not as effective as it should be. This is caused by several factors inhibiting local governments in carrying out these efforts, both in terms of finance (financial), facilities and infrastructure, as well as socialization that is still not given to the community. In the view of fiqh siyasa, the management and protection carried out by the local government of Jeneponto Regency are in accordance with Islamic law, because humans as caliphs on earth are to be able to prosper the earth in accordance with Islamic law.